Further antropological investigations in the Dakhleh Oasis (western desert, Egypt) - Dzierżykrzy-Rogalski, Tadeusz (Anthropological Review, 1981)
The author presents a progress of his rescarch obtained during the fourt Excovation Campaign (1980) at the Dakhleh Oasis. The research organized by l’Institut Prasgais d'Archenlogie Orientale, Cairo supplied already completely novel information on people of the Old Kingdom and later periods.